Призначення науки фінансового права: підходи до розуміння і трактування - Хохуляк, В'ячеслав Віссаріонович; Хохуляк, Вячеслав Виссарионович; Hohuljak, Vjacheslav (My University, 2011)
In the article the problems of determination of purpose are probed setting of science of financial law. Maintenance of the existent going opens up near understanding of setting of science of financial law. The human and objective factors of influence of science of financial law are characterized on legal and public practice.
Хохуляк В. В. Призначення науки фінансового права: підходи до розуміння і трактування / В. В. Хохуляк // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C.405-412.
Keywords: призначення науки фінансового права; наука фінансового права; фінансове право; предназначение науки финансового права; наука финансового права; финансовое право; the purpose of science of financial law; the science of financial law; financial right